Millennial Generation's Perception of Flexing and its Effect on Digital Asset Investment Decisions - Nyoman Suadnyana Pasek; Gusti Ayu Ketut Rencana Sari Dewi; Putu Arya Dharmayasa (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The purpose of this study is to identify the perception of the millennial generation which in this case is carried out on students about flexing. The analysis is continued by measuring the influence of the millennial generation's perception of interest in investing in digital assets. This research was conducted on students of the Accounting Program Faculty of Economics Undiksha. The results showed that the impact of Flexing was perceived as strong and met the expectations of the students. The perception of the millennial generation has a significant effect on the interest in investing in digital assets. Keywords: flexing, millennial generation, investment